A phenomonological study of class leaders - Finnegan, J. Michael (Kansas State University, 2013)
Learning communities are considered a high impact practice. Most research has focused on the benefits for the students within learning communities. This study sought to explore what learning community leaders learn from their experiences in a learning community. The central research question was: What do student leaders experience in a classroom learning community? A phenomenological qualitative research approach was used to explore this question. Twenty-five students who had recently been a leader of a learning community in a large lecture course at a Midwest landgrant university were interviewed. The participants reflected on their position as a class leader and described in detail their experiences. To analyze the data, significant statements from each of the transcripts were organized into meaning units. The meaning units were used to formulate two codes: (a) learning communities and (b) personal development. Seven themes emerged from the data: 1) environmental elements of a learning community, 2) responsibilities of a class leader, 3) class leader roles within a learning community, 4) caring relationships, 5) self-awareness, 6) vocation, and 7) impact. Participants described learning communities as a small group of diverse students engaged in the process of learning. Participants emphasized the need for a safe learning environment, and an environment that leaders need to cultivate. Skills that were developed from learning community leaders’ responsibilities include time management and small group facilitation and throughout the experience, leaders can look forward to the development of caring and long lasting relationships with students, other peer leaders, and faculty. Participants identified that being a learning community leader impacted one’s affective, cognitive, and behavioral development, all of which resulted in one’s self-understanding and self-confidence. The experience of being a learning community leader shaped or affirmed future plans and goals and strengthened one’s identity formation as a leader. The study explored the experiences of undergraduate student leaders in the classroom. The findings of this study challenged institutions to rethink large lecture classrooms and consider integrating learning communities within large lecture classes while being intentional to provide the necessary resources and support to train peer teachers who would be asked to lead the learning communities.
Keywords: Peer leaders; Learning communities; Leadership education; Educational leadership (0449)